The CHSE-214 salmon cell line as a model to study molecular regulation of long-chain polyunsaturated fatty acid biosynthesis in salmonids - Rubio Mejia, Olga Liliana (University of Stirling, 2015)
The main source of omega-3 (n-3) long-chain polyunsaturated fatty acids (LC-PUFA) in our diet is supplied by fish, and an ever-increasing proportion of these are being produced by aquaculture. The drive for the growing market demand and production from sustainable sources has led to the use of high-energy (fat) diets and, recently, to the replacement of fishmeal and fish oil with non-marine components, such as plant meals and vegetable oils that are devoid of n-3 LC-PUFA. Both changes impact greatly on lipid and fatty acid metabolism in fish, with health implications for the fish and the human consumer. This impact highlights the need to investigate the basic molecular mechanisms underlying the regulation of lipid and fatty acid metabolism in fish, specifically focussing on the pathways of lipid homeostasis and LC-PUFA synthesis. The aim of this study was to develop and utilise Chinook salmon embryo (CHSE-214) cell line as a model for Atlantic salmon, Salmo salar L., to enable an integrated approach to study the biochemical and molecular regulation of lipid metabolism in fish. In particular, α-linolenic acid (LNA, 18:3n-3) and linoleic acid (LOA, 18:2n-6), which are essential fatty acids abundantly found in vegetable oils, and are precursors of LC-PUFA, were supplemented in combination with other fatty acids, to explore the effect of these on total lipid content, lipid class, FA composition and gene expression of CHSE-214 cell line. Total lipid content was extracted, followed by determination of lipid class and fatty acid analyses. Gene expression analyses of transcription/nuclear factors and various target genes in Atlantic salmon, including those involved in pathways of LC-PUFA synthesis and fatty acid oxidation, were carried out. The results demonstrated that CHSE-214 cell line, under experimental conditions, is able to convert LNA to eicosapentaenoic acid (EPA, 20:5n-3), and LOA to arachidonic acid (ARA, 20:4n-6), but not LNA and/or EPA to docosahexaenoic acid (DHA, 22:6n-3), highlighting the activity of ...